Integration of Google Maps with database for e-museum web application - Mohd Isa, Badariah (2009)
Google Maps is a free web mapping service application and technology provided by Google that powers many map-based services including the. Google Ride Finder. Google Transit, and maps embedded on third-party websites via the Google Maps API. This research is focuses on the integration of Google Map with database for e-museum web-based application. It is also describes the requirements and processes needs for integrating the database with Google Maps to support the discovery of web-based services on the Website, and a prototype of e-museum. The combination of Google map with database improves the usefulness and functionality of the web-based location for museum. Besides, the purpose of this application is to help the travelers and tourist guides to find location plus the detail of information about a particular museum. This helps the traveler to manage time and get the correct information about museum. The emuseum web application develops in English language with the intention that, the foreign travelers can used this application as well. Thus, the integration of database to Google Maps could promote and support Malaysia's tourism industry especially for the travelers who love to go to museum.